(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The electrical transport and thermoelectric properties of Cu3Sb1-xAlxSe4 (x = 0, 0.03, 0.05 &0.07) compounds are investigated in the temperature range of (298 – 553) K. The results indicate that with increasing Al content from ( x = 0) to (x =0.07), hole concentration increases monotonically from (2.03×1018 to 2.82 × 1018 cm-3) due to the substitution of Al3+ for Sb5+, thus leading to a large decrease in the electrical resistivity of Cu3Sb1-xAlxSe4. Meanwhile, the increase in hole concentration leads to a transition from a non-degenerate (x = 0) to a partial degenerate (x = 0.05, 0.07) and then to a degenerate state (x = 0.07). The power factor (PF) of all the Al-doped Cu3Sb1-xAlxSe4 samples is remarkably improved due to the optimization of hole concentration. Lattice thermal conductivity kL of the heavily doped sample(x = 0.07) is reduced. As a result, a large thermoelectric figure of merit ZT = 1.28 is obtained for Cu3Sb0.97Al0.03Se4 at 458K, which is around 5 times as large as that of the un-doped Cu3SbSe4 sample.